Supply Chain Management in High-Tech Industries Clusterization: Market Monopoly or Development of Competitive Advantages? - Borisova, Viktoria; Shnyreva, Elena; Panfilova, Elena (International Journal of Supply Chain Management, 2020)
Abstract— With the rapid industrial cluster development, in particular the development of high-tech cluster, the supply chain management strategy in cluster is also undergoing profound changes. The study uses open-source statistical data, as well as research results and world rankings as the basis for a descriptive analysis of the external environment for the development of high-tech industries. Two main indicators were selected for the analysis: the GDP per capita growth rate and the level of information and communication development, which are used to assess competitiveness, the level of economic development, innovation and entrepreneurship. The purpose of the study is to examine the features of the innovation policy of developed countries and its impact on supply chain management in high tech industries for clustering them. As a result, it was concluded that the modern macroeconomic environment is characterized by digital transformation trends, as well as decreased geographical influences. Industrial supply chain managements are developed based on the interaction of environmental factors, demand conditions, production factors, and auxiliary industries.